Qualitative doctoral research in educational settings: Reflecting on meaningful encounters - Myria Pieridou; Maria Kambouri-Danos (International Journal of Evaluation and Research in Education (IJERE), 2020)
In qualitative doctoral research the methodological approach, and the research design are extremely important when ensuring the rigorousness of the work. This is particularly significant for all researchers, and even more for doctoral students who are still developing their research and analytical skills. This paper aims to support doctoral students in their research journey by highlighting some of the tensions involved in conducting qualitative research by unpicking the experiences of two doctoral students to learn from the concerns, questions and reflections on the use of qualitative methodology in their doctoral research projects. The findings reveal challenges and insights with regards to reflection, educational research and the developing identity of being a researcher. The paper discusses these reflections to support and guide doctoral students as early career researchers when planning and conducting qualitative research in educational settings.